2017
DOI: 10.1002/hep.29265
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐1 limits the progression of liver injury and promotes liver repair in acetaminophen‐induced liver injury in mice

Abstract: These results demonstrate that 2-O-sulfated domains in syndecan-1 HS halt disease progression and promote liver repair by enhancing hepatocyte survival in AILI. We propose that syndecan-1 is a critical endogenous factor that controls the balance between prosurvival signaling and apoptosis in hepatocytes in APAP liver disease. (Hepatology 2017;66:1601-1615).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 54 publications
(131 reference statements)
1
32
0
Order By: Relevance
“…In the decision making process MELD score is a helpful tool to establish the severity of the disease and predicts 3month mortality among patients with chronic liver disease waiting for transplantation [19]. In in vivo experiment syndecan-1 attenuated acetaminophen induced acute liver failure and promoted liver repair in mice [20]. In our study enhanced MELD score groups went together with higher amount of syndecan-1 on hepatocyte surface.…”
Section: Discussionsupporting
confidence: 49%
“…In the decision making process MELD score is a helpful tool to establish the severity of the disease and predicts 3month mortality among patients with chronic liver disease waiting for transplantation [19]. In in vivo experiment syndecan-1 attenuated acetaminophen induced acute liver failure and promoted liver repair in mice [20]. In our study enhanced MELD score groups went together with higher amount of syndecan-1 on hepatocyte surface.…”
Section: Discussionsupporting
confidence: 49%
“…The Akt/mTOR pathway is an important signaling pathway in regulating the intracellular homeostasis. It is reported that the activation of Akt signal pathway further can facilitate liver repair and regeneration [ 47 ] and attenuates APAP-induced liver injury [ 48 ]. A recent study has shown that activation of Akt/mTOR signaling pathway is essential in the inhibition of autophagy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of relevance of apoptosis in APAP‐induced hepatotoxicity is further supported by the evidence that the pan‐caspase inhibitor did not improve APAP‐induced liver injury . It should be noted that a small amount of apoptosis was observed in certain genetic knockout (KO) mouse strains such as syndecan‐1, liver specific Atg7 or Atg5 knockout mice . The apoptosis observed in these KO mice could be due to the secondary effects as a result of the deletion of the gene in the liver such as the activation of Nrf2 in liver‐specific Atg5 KO mice .…”
Section: Apap Metabolism and Hepatotoxicitymentioning
confidence: 97%
“…17 It should be noted that a small amount of apoptosis was observed in certain genetic knockout (KO) mouse strains such as syndecan-1, liver specific Atg7 or Atg5 knockout mice. [18][19][20] The apoptosis observed in these KO mice could be due to the secondary effects as a result of the deletion of the gene in the liver such as the activation of Nrf2 in liver-specific Atg5 KO mice. 19 Therefore, it should be cautious to interpret data obtained from gene KO mice in APAP-induced liver injury.…”
Section: C-jun N-terminal Kinasementioning
confidence: 99%